Insulinoma - Elsa S. Gaisina; Renata I. Karimova; Olga V. Malyshkina; Tatyana V. Nikiforova (Clinical Medicine (Russian Journal), 2026)
The article presents a description of a clinical case of insulinoma in a 69-year-old female patient. Insulinoma is a rare neuroendocrine tumor originating from the β-cells of the pancreas, the clinical manifestations of which are associated with hyperproduction of insulin/insulin-like factors, leading to the development of a hypoglycemic symptom complex. The presented case highlights the prolonged course and diagnostic difficulty of this disease due to its rare occurrence. The “gold standard” of diagnosis is the 72-hour fasting test, the purpose of which is to provoke the pathognomonic Whipple’s triad. Instrumental diagnostics of insulinoma include abdominal ultrasound and contrast-enhanced magnetic resonance imaging. The main method of treatment for benign insulinoma is surgical, with an effectiveness of 98–100%.